Place and role of «Seljuk Name» in the cultural heritage Kazakhstan and Central Asia (Journal of Oriental Studies, 2018)
Seljukname” in the cultural heritage of Kazakhstan and Central Asia isan urgent scientific task, primarily because of the need to explore the basicsocio-economic and political processes in the countries of this region onthe basis of historical and cultural source. Monuments are the link betweengenerations through the preservation and augmentation of the traditionsand distinctive cultural values. Study on cultural heritage through the prismof historical sources in our time is important.